Mucosal and Systemic Immune Responses to Salmon Gill Poxvirus Infection in Atlantic Salmon Are Modulated Upon Hydrocortisone Injection - Amundsen, Marit M.; Tartor, Haitham; Andersen, Kathrine; Sveinsson, Karoline; Thoen, Even; Gjessing, Mona C.; Dahle, Maria K. (Frontiers in Immunology, 2021)
Salmon Gill Poxvirus Disease (SGPVD) has emerged as a cause of acute mortality in Atlantic salmon (Salmo salar L.) presmolts in Norwegian aquaculture. The clinical phase of the disease is associated with apoptotic cell death in the gill epithelium causing acute respiratory distress, followed by proliferative changes in the regenerating gill in the period after the disease outbreak. In an experimental SGPV challenge trial published in 2020, acute disease was only seen in fish injected with hydrocortisone 24 h prior to infection. SGPV-mediated mortality in the hydrocortisone-injected group was associated with more extensive gill pathology and higher SGPV levels compared to the group infected with SGPV only. In this study based on the same trial, SGPV gene expression and the innate and adaptive antiviral immune response was monitored in gills and spleen in the presence and absence of hydrocortisone. Whereas most SGPV genes were induced from day 3 along with the interferon-regulated innate immune response in gills, the putative SGPV virulence genes of the B22R family were expressed already one day after SGPV exposure, indicating a potential role as early markers of SGPV infection. In gills of the hydrocortisone-injected fish infected with SGPV, MX expression was delayed until day 10, and then expression skyrocketed along with the viral peak, gill pathology and mortality occurring from day 14. A similar expression pattern was observed for Interferon gamma (IFNγ) and granzyme A (GzmA) in the gills, indicating a role of acute cytotoxic cell activity in SGPVD. Duplex in situ hybridization demonstrated effects of hydrocortisone on the number and localization of GzmA-containing cells, and colocalization with SGPV infected cells in the gill. SGPV was generally not detected in spleen, and gill infection did not induce any corresponding systemic immune activity in the absence of stress hormone injection. However, in fish injected with hydrocortisone, IFNγ and GzmA gene expression was induced in spleen in the days prior to acute mortality. These data indicate that suppressed mucosal immune response in the gills and the late triggered immune response in the spleen following hormonal stress induction may be the key to the onset of clinical SGPVD.